Return on Investment and Organizational Adoption - Grudin, Jonathan (CSCW'04, November 6-10, 2004, Chicago, IL., USA, 2004)
This paper considers the complexity of measuring the return on investment for technology adoption. A brief case study of technology adoption in a large design and construction firm provides a clear view of factors that came into play. The technology considered is simple; the apparent costs and benefits are relatively clear. Four parties are involved: diverse employees interested in using dual monitors, the information technology support group in the organization, an executive who had worked his way up from drafting, and employees of a software company that is considering expanding their support for dual monitor use. In the construction company, a seemingly logical and inexpensive hardware upgrade was subject to a wide range of technical and social pressures, some obstructing and others promoting adoption. Decisions are made in a manner that did not fit the model held by the product planners and designers in the software company.